Detection of macrophages engulfing cholesterol crystals and docosahexaenoic acid from spontaneous ruptured aortic plaque. Issue 5 (November 2022) - Noda, Hirotaka; Yutani, Chikao; Zaima, Nobuhiro; Komatsu, Sei; Iwa, Nobuzo; Takahashi, Satoru; Takewa, Mitsuhiko; Ohara, Tomoki; Kodama, Kazuhisa
Abstract: We visualized macrophages engulfing cholesterol crystals from spontaneously ruptured aortic plaques sampled by angioscopy. Docosahexaenoic acid cholesterol ester (DHA-CE) was demonstrated by imaging mass spectrometry. DHA-CE is reported to be produced by macrophages against inflammation. Activities of macrophages against atherosclerosis inside plaques was shown from spontaneously ruptured aortic plaques in situ . Learning objectives: Activities of macrophages such as engulfing cholesterol crystals and producing docosahexaenoic acid cholesterol ester were shown from spontaneously ruptured aortic plaques in situ .